A 3D cine‐MRI acquisition technique and image analysis framework to quantify bowel motion demonstrated in gynecological cancer patients. Issue 6 (7th April 2021) - Barten, Danique L.J.; Laan, Janna J.; Nelissen, Koen J.; Visser, Jorrit; Westerveld, Henrike; Bel, Arjan; de Jonge, Catharina S.; Stoker, Jaap; van Kesteren, Zdenko
Abstract : Purpose: Magnetic resonance imaging (MRI) is increasingly used in radiation oncology for target delineation and radiotherapy treatment planning, for example, in patients with gynecological cancers. As a consequence of pelvic radiotherapy, a part of the bowel is irradiated, yielding risk of bowel toxicity. Existing dose‐effect models predicting bowel toxicity are inconclusive and bowel motion might be an important confounding factor. The exact motion of the bowel and dosimetric effects of its motion are yet uncharted territories in radiotherapy. In diagnostic radiology methods on the acquisition of dynamic MRI sequences were developed for bowel motility visualization and quantification. Our study aim was to develop an imaging technique based on three‐dimensional (3D) cine‐MRI to visualize and quantify bowel motion and demonstrate it in a cohort of gynecological cancer patients. Methods: We developed an MRI acquisition suitable for 3D bowel motion quantification, namely a balanced turbo field echo sequence (TE = 1.39 ms, TR = 2.8 ms), acquiring images in 3.7 s (dynamic) with a 1.25 × 1.25 × 2.5 mm 3 resolution, yielding a field of view of 200 × 200 × 125 mm 3 . These MRI bowel motion sequences were acquired in 22 gynecological patients. During a 10‐min scan, 160 dynamics were acquired. Subsequent dynamics were deformably registered using a B‐spline transformation model, resulting in 159 3D deformation vector fields (DVFs) per MRI set. From the 159 DVFs, the average vector length was calculated per voxel to generate bowel motion maps. Quality assurance was performed on all 159 DVFs per MRI, using the Jacobian Determinant and the Harmonic Energy as deformable image registration error metrics. In order to quantify bowel motion, we introduced the concept of cumulative motion–volume histogram (MVH) of the bowel bag volume. Finally, interpatient variation of bowel motion was analyzed using the MVH parameters M10%, M50%, and M90%. The M10%/M50%/M90% represents the minimum bowel motion per frame of 10%/50%/90% of the bowel bag volume. Results: The motion maps resulted in a visualization of areas with small and large movements within the bowel bag. After applying quality assurance, the M10%, M50%, and M90% were 4.4 (range 2.2–7.6) mm, 2.2 (range 0.9–4.1) mm, and 0.5 (range 0.2–1.4) mm per frame, on average over all patients, respectively. Conclusion: We have developed a method to visualize and quantify 3D bowel motion with the use of bowel motion specific MRI sequences in 22 gynecological cancer patients. This 3D cine‐MRI‐based quantification tool and the concept of MVHs can be used in further studies to determine the effect of radiotherapy on bowel motion and to find the relation with dose effects to the small bowel. In addition, the developed technique can be a very interesting application for bowel motility assessment in diagnostic radiology.